Awareness Level and Attitudes regarding Breast Self-Examination and Breast Cancer among Women in Saudi Arabia (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: This study aimed to evaluate the attitudes and the level of awareness of women in Saudi Arabia regarding breast self-examination and breast cancer. Females must conduct breast self-examination regularly to observe any changes in their breast. Materials and Methods: This is a retrospective research that was conducted using a survey that was adapted from previously published studies conducted in Jordan and Northeast Nigeria. The questionnaire was validated by content validation and by face validation, and after that, the survey was prepared online using online electronic forms. Results: Approximately 95% of the respondents said that they are aware of breast cancer, mainly by social media (53.62%). The main risk factor of breast cancer, as reported by females, was family history (50.98%) followed by radiation exposure (35.04%). Change in the shape or size of the breast is the most common symptoms of breast cancer (66.93%). Moreover, 62.2 % of females stated that they heard about the self-examination but did not practice it. Conclusion: Although the females reported that their knowledge about breast cancer and self-examination was good, the majority did not practice breast self-examination. It is recommended to increase females’ awareness of breast cancer and self-examination by workshops, community services activities, and lectures.